The Bioethics National Commission in Chile: a pending task. Contributions from the experience of national bioethics commissions of Mexico and Italy - Ramos Vergara, Paulina; Arenas Massa, Ángela; Santos, Manuel J. (Acta Bioethica, 2015)
The aim of this study is to reflect on the origin, nature, integration and functions of National Bioethics Commissions of Mexico and Italy, with the goal to draw helpful experience for implementing the National Bioethics Commission in Chile. The study is qualitative-interpretative, phenomenological, descriptive and bibliographical. It is inferred that the National Bioethics Commission in Chile, in order to fulfill the function entrusted, it must consider the experience of other commissions, in particular that of Mexico and Italy.